Revision of the Lachnaia tristigma (Lacordaire, 1848) species-group (Coleoptera: Chrysomelidae) and description of a new species - Baselga, Andrés; Ruiz-García, Javier (Zootaxa, 2007)
The group of species of Lachnaia tristigma (Lacordaire, 1848) is revised. Previously known taxa and diagnostic characters are reassessed, yielding clear limits for species based on male and female genitalia and not on variable and overlapping external characters. A diagnosis along with figures of the median lobe of aedeagus, endophallus and spermatheca are presented for the previously known species, L. pseudobarathraea Daniel & Daniel, 1898 and L. tristigma, as well as the newly described L. gallaeca n. sp.